Improving Digital Content Production For Smes: A Design Science Approach To Ai-Integrated Workflow Development - Andika Rifki Afandi; Dina Dellyana (International Journal of Science and Environment (IJSE), 2026)
The study focuses on the redesign of a workflow related to the use of AI to produce content on Instagram to enhance the time-consumption, stability, and reliability of services provided to SME clients in Pallas Creative, a digital marketing agency. Because SMEs are starting to depend on Instagram as a source of awareness creation and a sales driving tool, the agencies are supposed to produce the necessary content in a timely and consistent way, but real-life issues like the incongruity of briefs, rewrites, and ineffective coordination tend to cause delays, rewrites, and inconsistent lead time. Thus, the inquiry that the proposed study is responding to is as follows: what can be done to design and implement an AI empowered content production workflow that would be less inefficient but remain efficient to the content quality and client satisfaction in an agency and SME environment? The qualitative Design science Research approach used in the study is backed by Business process management. Semi structured interviews were used to get the data with internal stakeholders into content operations and SME client representative integrated with observations and internal records. The as is workflow was mapped with the help of BPMN finding bottlenecks and revision loops, and the findings were structured with the help of the thematic analysis and root cause analysis and which were further translations into design requirements and principles in order to create the proposed workflow artifact. The findings include the information that the primary types of inefficiencies must be considered systemic (such as short ambiguity and weaponization of assets), but the approval and revision processes are prolonged and hindered by fragmented feedback, and operational end of a thread due to role dependency and frequent emergency demands. According to them, the suggested AI facilitates workflow introduces, introduces clearer governance about the revision and approval of any work in a single gate approval and structured feedback, centralized tracking and versioning as a single source of solidity, a dual-lane production flow of planned and momentum content flow, and human-in-the-loop AI support with short development and ideating drafting and quality checks. In general, this paper gives a viable workflow map that can assist organizations attending to SMEs to streamline lead time and rework and still maintain consistency and reliability of services.